2016
DOI: 10.1097/igc.0000000000000686
|View full text |Cite
|
Sign up to set email alerts
|

MiR-195 Suppresses Cervical Cancer Migration and Invasion Through Targeting Smad3

Abstract: The newly identified miR-195/Smad3 pathway provides an insight into cervical cancer metastasis and may represent a novel therapeutic target.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(59 citation statements)
references
References 29 publications
5
53
0
1
Order By: Relevance
“…Almeida et al reported that overexpression of miR-195 led to a decrease in osteogenic differentiation and proliferation rate in human primary mesenchymal stromal/stem cells (MSC) [55]. Zhou and colleagues reported that miR-195 suppressed cervical cancer migration and invasion through targeting Smad3 [56]. In the present study, we found that miR-195 was elevated in joint fluid specimens of patients with chronic cartilage lesions and in CH1M/CH3M chondrocytes.…”
Section: Discussionsupporting
confidence: 60%
“…Almeida et al reported that overexpression of miR-195 led to a decrease in osteogenic differentiation and proliferation rate in human primary mesenchymal stromal/stem cells (MSC) [55]. Zhou and colleagues reported that miR-195 suppressed cervical cancer migration and invasion through targeting Smad3 [56]. In the present study, we found that miR-195 was elevated in joint fluid specimens of patients with chronic cartilage lesions and in CH1M/CH3M chondrocytes.…”
Section: Discussionsupporting
confidence: 60%
“…The function of miR-195 in CC has been widely probed, and it is certified that miR-195 inhibits CC cell proliferation, invasion and migration by targeting related genes, while the knockdown of miR-195 has the opposite impact on cell processes [3,6,24,25]. In this study, we further demonstrated that miR-195-5p could lessen CC cell proliferation and invasion ability via targeting MMP14.…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andsupporting
confidence: 49%
“…In previous studies, miR-195 has been found down-regulated significantly in CC tissues and cells [2,6]. For example, Zhang et al have reported miR-195 as a novel biomarker for detection of CC [5].…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, miR-16-2-3p has been shown up-regulated in serum pointing out the role of miR-16 in cervical carcinogenesis [40]. On the other hand, miR-195 is shown down-regulated in cervical cancer and its overexpression inhibits proliferation, G1-S transition, migration and invasion through Cyclin D1, Cyclin D2, MYB proto-oncogene, transcription factor (MYB) and Smad 3 down-regulation via 3′UTR [44,45,46,47]. …”
Section: Oncogenic Mir-15 Family Participates In Cervical Cancermentioning
confidence: 99%